Efeitos da neuromodulação associada à fisioterapia sobre sintomas da fibromialgia e seus correlatos eletroencefalográficos - Melo, Géssika Araújo de (2022)
Fibromyalgia (FM) is a condition in which chronic widespread pain is present, characterized by fatigue, sleep disturbances, and comorbidities such as anxiety and depression. Given the complexity of FM, transcranial direct current stimulation (tDCS) emerges as an important technique, complementary to physical therapy, capable of modulating cortical electrical activity and providing additional benefits to conventional treatment. In this study, structured as 11 articles, we analyzed the clinical characteristics of FM and the effects of neuromodulation associated with physiotherapy on symptoms of FM and its electroencephalographic correlates. Initially, we analyzed the sociodemographic and clinical profile of the FM participants in the study. We also discussed how the electroencephalogram (EEG) can help in the evaluation and response to treatment and the possible correlation between clinical symptoms, such as pain, anxiety and depression, and cortical activity in FM. Regarding treatment, physiotherapy resources were analyzed as a form of conventional treatment to maintain functionality and quality of life in this population, as well as the applicability of tDCS for psychological symptoms in FM. The empirical study consisted of a randomized clinical trial that analyzed the effects of tDCS as a complementary treatment to physiotherapy in the treatment of FM symptoms. Overall, the results indicate that EEG may be a promising resource for evaluating and monitoring treatment response in women with FM. In the empirical study, it was observed that tDCS can be considered a technique that can assist in improving pain perception, anxiety, and depression in women with FM.